Ukuran Populasi Kroto dan Tumbuhan Inang Semut Rangrang di Hutan Pantai Moinit Kabupaten Minahasa Selatan - Yunias Wenda; Frans T; R Kainde (COCOS, 2017)
ABSTRAKKroto is an ant egg rangrang and is the result of non-timber forest. Kroto is useful for birds chirping food and fish bait. Excessive utilization will cause the ant population to decrease. Rangrang ants also play a role to preserve the forest because it is a predator of certain pests.The research was conducted in Moinit coastal area of South Minahasa regency in November-December 2016. This study aims to find out the population of kroto and plant species ant ant rangrang. The method used is to record all the trees contained nests and purposive to determine the sample. The results of the study were 6 species of host plants from the ant rangrang namely ketapang (Terminalia cattapa),mengkudu (Morinda citrifolia L.), urlaut star (Calophyllum inophyllum), bitter tree (Barringtonia asiatica), waru (Hibiscus tiliaceus L.), banyan tree (Ficus benjamina L) .Number of nest / type of host plant, nest of ketapang 5 nest, mengkudu 3 nest, 4 nest urlaut, nest of bitung 5 nest, waru 4 nest, banyan tree 7 nest. The average number of hatchlings / species of host plants consists of ketapang 46,68 cm, mengkudu 40,57 cm, urlaut star 44, 51cm, tree bitung 41,71 cm, waru 48,36 cm, 36 cm cold tree. The average number of shoots / nests / granaries is exposed to cramped 74 kroto, mengkudu 75 kroto, urlaut 74 kroto, mengkudu, bitung 75 kroto, waru 78 kroto, banyan tree 38 kroto. Keywords: Kroto, non timber forest products, forest….